1998
DOI: 10.1080/10759419808945903
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Mode Delamination of Multidirectional Carbon Fiber/Epoxy Laminates

Abstract: SUMMARYScanning electron microscopy was used to identify fractographic features that are characteristic of different modes of interlaminar fracture. The cusp angle and the amount of fibre pull-out on the fracture surface can be used to characterise the different loading modes.A large amount of fibre pull-out is the dominant feature of a mode I fracture whilst in mode II large cusp angles and many cusps are the main characteristics. The amount of fibre pullout, and subsequently broken fibres, per unit area was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 36 publications
(32 reference statements)
0
19
0
Order By: Relevance
“…It has been shown that the fracture toughness of some adhesively bonded systems is independent of mode-mixity [6]. It may also be the case that an increase in the mode I component of the mixed-mode fracture toughness can occur as percentage mode II increases, particularly during interlaminar fracture [7,8]. The scrim cloth used in numerous film adhesives (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…It has been shown that the fracture toughness of some adhesively bonded systems is independent of mode-mixity [6]. It may also be the case that an increase in the mode I component of the mixed-mode fracture toughness can occur as percentage mode II increases, particularly during interlaminar fracture [7,8]. The scrim cloth used in numerous film adhesives (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…However, the inter-laminar stresses within laminated materials are localised at interfaces due to the strong discreteness in the material properties. This localisation of stress can lead to delamination and crack propagation [4][5][6]. To eliminate the stress localisation, a proper continuous gradient is required to smooth the property transition 3 through the thickness.…”
Section: Introductionmentioning
confidence: 99%
“…The cusps in the different fracture modes also stood more upright (i.e. the cups angle was larger) than the cusps previously observed in epoxy matrices [21,25].…”
Section: Fracturementioning
confidence: 84%
“…8. The formation of cusps has been attributed to a brittle failure of the matrix [17][18][19][20][21] and can be described as the coalescence of brittle microcracks which form perpendicular to the resolved principal stresses just ahead of the crack tip, as shown schematically in Fig. 9.…”
Section: Fracturementioning
confidence: 99%